Amyloid β-Induced Nerve Growth Factor Dysmetabolism in Alzheimer Disease - Bruno, Martin (2009)
We have reported that the precursor form of nerve growth factor (proNGF) and not the mature NGF is liberated in the CNS in an activity-dependent manner and that its maturation and degradation occurs in the extracellular space by the coordinated action of proteases (Bruno & Cuello, 2006). In this report we communicate evidence for a diminished conversion of the NGF precursor molecule to its mature form as well as evidence for an increased NGF-degradation in Alzheimer’s brain samples. These alterations of the NGF metabolic pathway result in an up-regulation of proNGF levels. In these Alzheimer’s brain samples we have also found that the elevated proNGF occurs largely in a peroxynitrated form.  The intrahippocampal injection of Aß-oligomers provoked a similar up-regulation of proNGF in naïve rats, along with microglia activation, increased levels of inducible nitric oxide synthase (iNOS) and hyperactivity of the NGF degrading enzyme MMP-9. The elevated iNOS provoked the generation of biologically inactive; peroxynitrite-modified proNGF in Aß oligomer-injected rats.  These parameters were corrected with the application of minocycline.  The application of minocycline in a transgenic AD mouse model also diminished altered MMP-9, iNOS and microglial activation, preserving cognitive behavior and normalizing proNGF levels. These effects of Aß amyloid CNS burden on NGF metabolism would explain the well-known and paradoxical up-regulation of proNGF in Alzheimer disease, accompanying by atrophy of forebrain cholinergic neurons.